Electrical Behavior of Polyurethane Derived from Polyols Synthesized with Glycerol, Phthalic Anhydride, and Oleic Acid - Velayutham, T.S.; Abd Majid, Wan Haliza; Gan, S.N. (Wiley, 2011)
The direct current (DC) and alternating current (AC) conductivity of polyurethane (PUR) derived from polyols synthesized with glycerol, phthalic anhydride, and oleic acid were investigated in this article. The PUR was prepared by varying the oleic acid content in polyol (28, 40, and 65) and the NCO/OH ratio of the PUR was varied to 1.2, 1.4, and 1.6. The electrical conduction studied by measuring the dependence of current on the applied field and temperature. Electrical conductivity in PUR was expressed by Arrhenius relations and the activation energies were calculated. Moreover, hyperbolic sine function was used to determine the conduction mechanism in PUR. It's presumed that the conduction mechanism was assisted by ions for the PUR which were contributed by oleic acid due to dissociation of protons and highly polar urethane groups in PUR. Furthermore, the dielectric behaviors of the material have been measured at room temperature in the frequency range of 100 Hz to 40 MHz. The frequency-dependent conductivity of PUR materials has been analyzed using a Jonscher's power law expression and the plot exhibits the typical behavior of ionic materials, i.e., the DC plateau and the frequency dependent region. Â© 2011 Wiley Periodicals, Inc.